2013
DOI: 10.2967/jnumed.112.112508
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Intratumoral 99mTc-Macroaggregated Albumin Uptake in Patients with Colorectal Liver Metastases Scheduled for Radioembolization with 90Y-Microspheres

Abstract: 90 Y radioembolization is a promising therapy for patients with primary and secondary liver malignancies. Pretherapeutic assessment consists of hepatic angiography and 99m Tc-macroaggregated albumin ( 99m Tc-MAA) perfusion scintigraphy to estimate the liver-to-lung shunt and exclude extrahepatic 99m Tc-MAA deposition. However, the predictive value of intratumoral 99m Tc-MAA uptake remains unclear. Methods: One hundred four patients with chemotherapy-refractory liver-dominant metastatic colorectal cancer were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 35 publications
(41 reference statements)
6
64
0
2
Order By: Relevance
“…Although it has been noted that the PM would be the preferred method of 90 Y-RE for every patient [55,56], its main drawbacks are the reliance on segmentation of tumour/non-tumour for activity determination and dosimetry purposes, and the assumption of concordance between the MAA (from which the TN ratio is calculated) and MS distribution. This assumed equivalency is a fact much disputed by recent studies, especially in liver metastases [57,58] and is described further below. In clinical scenarios, the PM and GMS equations are employed mainly in patients with hypervascular, large and numerically limited lesions, such as HCC.…”
Section: Limitations Of Current Dosimetry Modelsmentioning
confidence: 94%
See 2 more Smart Citations
“…Although it has been noted that the PM would be the preferred method of 90 Y-RE for every patient [55,56], its main drawbacks are the reliance on segmentation of tumour/non-tumour for activity determination and dosimetry purposes, and the assumption of concordance between the MAA (from which the TN ratio is calculated) and MS distribution. This assumed equivalency is a fact much disputed by recent studies, especially in liver metastases [57,58] and is described further below. In clinical scenarios, the PM and GMS equations are employed mainly in patients with hypervascular, large and numerically limited lesions, such as HCC.…”
Section: Limitations Of Current Dosimetry Modelsmentioning
confidence: 94%
“…In many metastatic cases, clear definition of the tumour boundaries proves difficult due to diffuse metastatic spread and differing vascularity [5], and therefor the PM proves difficult to apply. Recent work shows it cannot be recommended in general for patients with liver metastases [57,59]. This model also disregards the spatial and temporal variation of the dose, dose rate and radiobiological effects, providing a simplified picture for patient dosimetry [60].…”
Section: Limitations Of Current Dosimetry Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, their results were primarily obtained with resin microspheres in a metastatic disease context, for which several previous studies reported disappointing results [12,13], probably due to several parameters, including the disease's multifocality. This difference can be explained by the fact that Lam et al took care to only include patients with exactly identical catheter positioning between diagnostic and therapeutic angiography.…”
mentioning
confidence: 99%
“…Several groups have discussed discordant accumulation patterns for both substances [7][8][9]. Just recently, we have published a patient series where Tc-99m-MAA accumulation in colorectal liver lesions did not correlate with clinical response [10]. In light of these assumptions supplemented by the different morphology of lung tissue compared with liver the eligibility of the Tc99m-MAA as surrogate for radioembolization of lung malignancies must be reevaluated.…”
mentioning
confidence: 99%